1996
DOI: 10.1038/382716a0
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor-mediated adhesion of microglia to β-amyloid fibrils

Abstract: A pathological hallmark of Alzheimer's disease is the senile plaque, containing beta-amyloid fibrils, microglia and astrocytes. Beta-amyloid fibrils exert a cytotoxic effect on neurons, and stimulate microglia to produce neurotoxins, such as reactive oxygen species. Mononuclear phagocytes, including microglia, express scavenger receptors that mediate endocytosis of oxidized low-density lipoproteins, and adhesion to glucose-modified extra-cellular matrix proteins. Here we report that class A scavenger receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
539
1
5

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 724 publications
(557 citation statements)
references
References 18 publications
12
539
1
5
Order By: Relevance
“…3 C and D, respectively). As MSR has been proposed as a microglial receptor for A␤ (41) and is also expressed at increased levels in AD (42), this suggests a mechanism whereby neuronal stimulation of RAGE could enhance subsequent microglial-A␤ interaction. M-CSF also enhanced BV-2 cell expression of apoE, as shown by the increased level of antigen (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 C and D, respectively). As MSR has been proposed as a microglial receptor for A␤ (41) and is also expressed at increased levels in AD (42), this suggests a mechanism whereby neuronal stimulation of RAGE could enhance subsequent microglial-A␤ interaction. M-CSF also enhanced BV-2 cell expression of apoE, as shown by the increased level of antigen (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with a mechanism involving membrane receptors, we have shown that the lectin ConA, which forms clusters of membrane glycoproteins on the cell surface, also causes neurodegeneration and apoptotic death in cultured neurons similar to that observed with A␤ while succinyl ConA, which binds but does not cross-link, is inactive (39). Recently, Burdick,et al (40) have shown that a substantial portion of the A␤ that binds to cells can be removed by treatment with trypsin and several receptors that appear to bind A␤ peptides have been identifed (41)(42)(43)(44)(45)(46). In the case of the receptor for advanced glycation end products (RAGE), some evidence has been presented that it may be directly involved in A␤-induced neurotoxicity (45).…”
Section: Discussionmentioning
confidence: 99%
“…Brain and microglial up-regulation of PRRs members has been observed in human and experimental AD ( [3,67,21,258]). The Ab peptide was shown to activate microglia cells through the interaction with specific PRR: (a) scavenger receptors, including scavenger receptor class-A (SR-A), SR-B1 and CD36, that mediate Ab endocytosis and induce ROS production ( [46,66]); (b) macrophage receptor with collagenous domain (MARCO), a scavenger receptor that mediates adhesion of Ab to microglia and the cytoskeleton rearrangements induced by this peptide [84]; (c) the receptor for advanced glycation endproducts (RAGE), a member of the immunoglobulin superfamily, responsible for the induction of the inflammatory response stimulated by Ab ( [6,143,258]). …”
Section: Animal Models Of Alzheimer's Diseasementioning
confidence: 99%